Crowned dens syndrome presenting as pyrexia of unknown origin (PUO) - Bansal Agam; Gupta Mohit (Sciendo, 2019)
Background. Deposition of calcium pyrophosphate crystals in the cervical spine around the odontoid process may lead to neck pain and fever. This condition is called crowned dens syndrome (CDS).